Study of 2-input 2-output Blind Signal Separation by Output Decorrelation - Machuca, E.; Sovka, Pavel; Davidek, V. (Radioengineering Society, 1998)
The simulations and experiments representing the initial study of the output decorrelation approach to blind signal separation are presented in this paper. The definition of performance indexes for the evaluation and comparison of different algorithms are proposed. Two algorithms are compared. Some first results of real experiments are discussed.
Keywords: blind signal separation; output decorrelation; synmetric adaptive decorrelator